UPAYA GURU DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN DENGAN MEDIA KARTU HURUF DI MADRASAH IBTIDAIYAH CIBUNGBULANG KABUPATEN BOGOR - Qurotaa’eni, Ilfa; hasanah, tita; Nugraha, Acep (JURNAL KAJIAN ISLAM MODERN, 2024)
This research aims to improve children's reading skills at Madrasah Ibtidaiyah (MI) Darul Muttaqin. The method used in this research is collaborative classroom action research using the Kemmis and Mc Taggart model through three stages, namely planning, implementation and reflection. The subjects of this research were 23 second grade students at MI Darul Muttaqin, Cibungbulang District, Bogor Regency. The data collection methods used are observation and documentation. The data analysis technique was carried out descriptively. The success indicator set is a minimum of 75% of the total number of second grade students. This research was conducted in two cycles using letter card media. In the pre-cycle implementation, the score was 45.76%, in cycle 1 the score increased to 52.72%, and in cycle 2 it improved with a percentage of 79.13%. The results of the research showed that the initial reading skills of second grade students improved after carrying out two action cycles using letter cards as media, which was observed in the aspects of language, knowledge, language awareness and cognitive skills.